Usury Agreement and Modern Methods to Apply it in the Islamic Financial System - Abdurahmanov, Gafgaz (Scholarya Demo Journal of Ruby, 2022)
The usury agreement that provides for the delivery of goods by a seller to a buyer on a specified date in the future in exchange for a cash payment is one of the types of sales permitted under Islamic law. Although this type of sale is contrary to the rule of Islamic Law prohibiting the sale of non-existent goods, it is exclusively permitted due to the need of people in it. Therefore, unlike other types of sales, the usury agreement has some specific terms and conditions. It its early times, the sale through usury was only used to trade agricultural goods. Later, with the development of Islamic financial institutions, this type of sales began to be used in industry and trade, especially in agriculture. It should be noted that the usury (riba) agreement is considered one of the most important transactions of Islamic banks in modern times. Due to its specific characteristics, Islamic financial institutions use this type of sale as one of the alternatives to interest-bearing agreements applied by traditional banks. The key goal of this Thesis is to explore areas where sales through usury can be applied in our time. As it differs from other types of sales, the Thesis first describes the definition and specific terms of the usury agreement, and then discusses the areas and methods of application of this type of sale by Islamic financial institutions. The Thesis ends with findings.